ANALISIS SISTEM DU PONT DAN PENGARUHNYA TERHADAP HARGA SAHAM PADA EMITEN STARTUP DI BEI - Ambardi Ambardi; Aam Aminah; Adi Rizfal Efriadi; Rizky Maulana Pribadi (UNIVERSITAS PGRI MADIUN, 2024)
Abstract : The aim of this research is to determine the influence of variables from the Dupont analysis system on share prices in startup issuers. This research method is to use a panel data regression model. The data analysis technique used in this research is descriptive statistical analysis and quantitative statistical analysis. Next, the model selection test was first carried out using the Chow, Hausman and LM tests. Descriptive statistical analysis is used to describe the variables in this research, namely Total Assets Turnover (TATO), Net Profit Margin (NPM), Return on investment (ROI) and share value. Meanwhile, quantitative statistical analysis is used when testing hypotheses, namely partial testing (t test). From the results of this research, it can be concluded that there is no significant influence on either net profit margin, total asset turnover or return on investment on share prices in startup issuers. Apart from that, it was also found that there was very little relationship between the variables used in the du pont system analysis and the share prices of start-up issuers.